Nonlinear dynamics. proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 /: proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017. Volume 1 : (2017) - Unknown
No abstract available